CHARACTERISTICS OF THE OTTOMAN TRADITIONAL HOUSES IN THE LIBYAN OLD CITY OF GHADAMES: CASE STUDY OF DA BABANEI HOUSE - Ahmed Ameen (Fayoum University, 2016)
Ghadames, lies in an oasis, is located at the most western Libyan populated city near the bounders with Tunisia and Algeria. Now it is known as the city of Ghadames, of which the old walled city represents a unique example of the covered pre-Sahran cities in the world. This paper aims to study the ottoman domestic architecture in Ghadames in the light of author’s visit in 2014, with special focus on the house of DA BABANI, or Hadji Abdul Salam Shemila house (the current owner), as a case study. It is dates back before the 12th A.H./18th century C.E. The exterior of the houses of Ghadames is simple and non-adorned while few of them have small and high windows. Foundations and walls, upmost one meter high, are constructed of sandstone, while the rest of the walls are of mud bricks. Palm wood is used extensively in Ghadames houses for both construction and decoration. Ghadames houses are characterized by a vertical division of functions: the ground floor (or level), used to store supplies; then the main floor for the family, and, at the top, there is an open-air terrace comprising the cooking-place (kitchen). Ghadames house includes, from the architectural spaces point of view, stores, main reception hall, living places, a kebba (a small room with a specific use, only on two occasions, by the lady of the house), a toilet, a kitchen and passageways and stairways as well. The most characteristic features of the traditional Ghadames house that there is no an open-air internal courtyard; which gives the houses of Ghadames those main features comprising the vertical division. Also there is a unique use of the open-air terraces, at the top of the houses, which reserved for the women, and used as a network of passageways connecting all the houses of the old walled city of Ghadames. Also, the form and content of the decoration characterize the Ghadames house. Furthermore, this paper discusses the influences of the Sharia (Islamic rules or Fiqh) on the design of the Ghadames house, and illustrates the precise features of the pre-Sahran traditional domestic architecture of Ghadames in the light of its comparison with more alike settlements clarifying the similarities and differences as well.